Isaria tenuipes Peck, an entomopathogenic fungus from Darjeeling Himalaya: Evaluation of in-vitro antiproliferative and antioxidant potential of its mycelium extract - Dhani Raj Chhetri; Abhijit Chhetri; Nerina Shahi; Snigdha Tiwari; Shibendra Kumar Lal Karna; Dorjay Lama; Yuba Raj Pokharel (BMC, 2020)
Abstract Background Isaria tenuipes is one of the potent species in the members of the genus Isaria, which is well reported to possess multiple bioactive substances of therapeutic importance. Therefore, an in vitro experimental study was carried to evaluate the bioactivities of the crude methanolic extract from the mycelium of this fungus. Methods The fungus was authenticated through morphological characters and the species discrepancy was resolved using the nuclear rDNA ITS sequence. The methanolic extract was fingerprinted by FTIR. The antioxidant components in terms of total phenols and flavonoids were determined as gallic acid and quercetin equivalents respectively. Antioxidant activities of the methanolic extract was assessed using 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2, 2/-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid) radical cation (ABTS0+), Fe2+chelating activity, and hydroxyl radical scavenging assays. Cytotoxicity of the extract was determined by [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] (MTT) assay on three cancer cell lines: HeLa, HepG2, and PC3. Apoptosis was further studied by propidium iodide (PI) and Annexin-V/PI staining flow cytometric analysis. Anti-proliferation capacity was studied by colony-forming assay. Results In the present study total phenol content of the dried methanol extract was 148.09 ± 3.51μg gallic acid equivalent/mg and flavonoid was 9.02±0.95 μg quercetin/mg. The antioxidant activities of methanol-water extract (8:2 v/v) from cultured mycelia of I. tenuipes investigated and evaluated with 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay revealed IC50 value of 5.04mg/ml with an inhibition rate of 74.77% at 10mg/ml and with an iron-chelating assay the chelating ability was recorded to be 86.76% where the IC50 value was 4.43 mg/ml. In comparison among the antioxidant assays, 2,2/-azinobis-(3-ethylbenzthiazoline-6-sulphonic acid) radical cation (ABTS0+) and hydroxyl assay exhibited radical scavenging rate of 44.42% and 49.82% respectively at a concentration of 10 mg/ml. The IC50 value of the extract in MTT assay was 43.45μg/ml with HeLa cells, 119.33μg/ml with PC3 cells, and 125.55μg/ml with HepG2 cells. Conclusion In this study, it can be concluded that the crude methanolic extract exhibited potent antioxidant and antiproliferative activities suggesting natural antioxidative and antiproliferative agents.